Effect of the windshield perforation patterns on the cooling performance in centrifugal separators - Kim, Young Min; Lee, Kwang-Hee; Chung, Sang-Min; Lee, Daeyup; Yoo, Youngil; An, Chang Sung; Lee, Chul-Hee (Journal of mechanical science and technology, 2024)
The cooling performance of a centrifuge was enhanced using a perforated windshield. The windshield spatially separates the rotor and the chamber, reducing turbulence and air resistance. On the other hand, during centrifuge rotation, heat is generated by friction between the internal structure and air. Optimizing the windshield shape and facilitating efficient heat exchange with the chamber wall are essential for cooling the sample container inside the windshield. This study examined the cooling performance of the perforated windshield through analysis and experiment. The effects of the presence, location, and diameter of the perforations were compared using computational fluid dynamics (CFD) simulations and considering temperature and flow characteristics. These results suggest that the perforated windshield enhances the cooling performance of the centrifuge.